The Courier de l’Europe, The Gordon Riots and Trials, and the Changing Face of Anglo-French Relations - Howard Weinbrot (Etudes Epistémè)
The Courier de l'Europe supported American independence, the free press that flourished in Britain, and the parliamentary system that pitted loyal opposition against the government's ministry. The Courier nonetheless harshly editorialized regarding “Protestant” hostility to the 1778 Catholic amelioration act and London's consequent and destructive Gordon Riots in June of 1780. By 1786 and Lord George's two trials for libel, its judgment of him moves from anger different only in degree from British anger, to rage, name-calling and cries that the maniac belongs in Bedlam. This paper traces some of this movement, suggests that it is a function of the courier's editorial changes from Serres de la Tour and Brissot to Warville, to Charles Thévenau de Morande, and draws inferences regarding French perception of Britain in the later eighteenth century.